PENGARUH MOTIVASI DAN PERSEPSI PELAYANAN TERHADAP KETERATURAN ANTENATAL CARE PADA IBU HAMIL DI PUSKESMAS NGEMPLAK SIMONGAN KOTA SEMARANG PADA TRI WULAN I TAHUN 2015 - Nery Ermaya; Raden Djoko Nugroho; Dharminto Dharminto (Jurnal Kesehatan Masyarakat (Undip), 2017)
Maternal mortality became one of the important indicators in measuring the degree of public health. Maternal and perinatal health problem is also a problem that needs to get top priority, semarang city ranked fifth highest in Central Java after the town of Brebes, Tegal, Cilacap and Banyumas with maternal mortality of 109,2 per 100,000 live births or 29 cases of maternal deaths by 2013. This research aims to analyze the influence of motivation and perception of service to the regularity of antenatal care in pregnant women at Puskesmas Ngemplak Simongan Semarang city in the first quarter 2015. The method used was Explanatory Research with approach of Cross Sectional Study time. The sample used is 36 mother birthing in January – March 2015, out of a total population of 44 of the mother of the baby. Data analysis includes the univariate analysis and bivariat (descriptive and anlitik) using Correlation Product Moment and multiple linear regressions with α 5%. The results of the univariate motivational variables shows the values of r = 0,639 with significance (sig) for 0.000 (significance < 0.05), it means there is a strong relationship between postiif varibel the motivation with the regularity of antenatal care. On the variable perception of service indicating the value of r = 0,852 with significance (sig) for 0.000 (significance < 0.05), it means there is a strong relationship between postiif varibel perspesi service with the regularity of antenatal care. Multiple regression analysis on obtained results that the regularity of the ibu antenatal care in the conduct of 74,9% influenced by motivation and perceptions of service. Based on the results of the test t, then obtained a Ministry that perception is a free variable that has a value of highest influence (72.1%), motivational variables (23.4%). The granting of an understanding about the importance of health in antenatal care to improve perceptions of both pregnant women against the health service.